MAPPING SYSTEM AND PHOTOGRAMMETRIC PROCESSING METHOD FOR TETHERED BALLOON PLATFORM - J. M. Li; J. M. Li; C. R. Li; G. Z. Su; W. Li; L. L. Ma; Y. K. Liu (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2019)
As a platform with the advantages of safety, wide altitude range and long flight time, tethered balloon has been used in archaeology, coastal, island mapping and other related fields. Tethered balloon is tied to the mooring system by tether rope, and often moves in a small range with the airflow, resulting in a very close distance between the camera stations. Due to the small base-to-height ratio, failure of relative orientation or poor quality of point cloud tend to appear frequently. In this paper, a mapping system for tethered balloon is introduced which consists of a wide-angle camera, two auxiliary orientation cameras, and a dual GNSS/IMU system. The wide-angle camera combined by five cameras provides a larger observation range. Two auxiliary orientation cameras installed at the end of extension rods are designed to increase the baseline. The system should be operated during the taking-off, hovering and landing stages of the tethered balloon, so as to take images of different altitudes. The system has been adopted in the first experimental flight in 2018 to perform island topographic survey. Data processing method was applied to test the effect of the system. The method that choosing wide-angle images of different heights, and auxiliary images at low-altitude can be used for aerial triangulation successfully, and obtain point cloud with good quality. The results showed that by adding auxiliary cameras and taking images of different heights for data processing, the problem of small intersection angle could be overcome to some extent.